2021
DOI: 10.1002/asia.202101239
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Involved Ring‐Opening of 4‐Phenyl‐1,2,4‐triazoline‐3,5‐dione for “Photo‐Clicked” Access to Carbamoyl Formazan Photoswitches In Situ

Abstract: Cyclic azodicarbonyl derivatives, particularly 4phenyl-1,2,4-triazoline-3,5-dione (PTAD), commonly serve as arenophile, dienophile, enophile and electrophile. Perplexed by its instability in aqueous environment, there are few studies focused on the transient intermediate produced by hydrolysis of PTAD to achieve synthetic significance. Herein, we describe a "photo-click" method that involves nitrile imine (NI) from diarylsydnone to capture the diazenecarbonylphenyl-carbamic acid (DACPA) generated by water-prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…A plausible reaction mechanism was also proposed based on previous research 17 and calculations, as shown in Fig. 5b.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…A plausible reaction mechanism was also proposed based on previous research 17 and calculations, as shown in Fig. 5b.…”
Section: Resultsmentioning
confidence: 85%
“…4-Phenyl-1,2,4-triazoline-3,5-dione (PTAD) has served as a highly reactive dienophile or electrophile in various chemical transformations, 17 and has been utilized for bioconjugation of tyrosine 18 and tryptophan 19 residues on proteins. Back in 1976, 20 vinyl azides (VAs) were utilized as diene surrogates for ring formations with PTAD, affording a unique bicyclic triazoline 20 in which the electron-deficient –NN– moiety in the PTAD was transformed into an electron-rich dihydrazide kernel.…”
Section: Introductionmentioning
confidence: 99%